PHARMACEUTICAL QUALITY AUDITS: A REVIEW - Agarwal, Princy; Mishra, Amul (International Journal of Applied Pharmaceutics, 2019)
Auditing is a vital function within a pharmaceutical company nowadays. Quality audit is a review and evaluation of all or part of a quality system with the specific purpose of improving it. It is one of the means to examine pharmacy programs and ensures that the procedures and reimbursement mechanisms comply with the contractual and regulatory requirements. A quality audit is usually conducted by external or independent experts or by a team designated by management for this purpose. These audits can be extended to suppliers and contractors as well. An audit will assess the strengths and weaknesses of quality assurance and quality assurance processes, the results of which assists in improving processes and building a better system for company benefits. This article focuses on various aspects of quality auditing in the pharmaceutical industry including its principles, objectives, importance and benefits and planning along with the deficiencies that are likely to occur during the process. This review comprises a well-organized summary of various guidelines available till date using the Google Scholar search engine and the keywords listed below.